Formation of the bases of professional pedagogical activity in the professional training of the teacher of technology - Нevko I. V. (Journal of Education, Health and Sport, 2017)
The article analyzes the scientific and pedagogical literature of the problem of professional competence of the modern technology teacher and defines the foundations for the formation of professional pedagogical activity in the vocational training of technology teachers. The experience of leading European scientists in the development of the concept of professionally pedagogical activity is considered. The main components of the competence of the training of future teachers of technology for the general education school are determined.